Environmental sustainability as a dimension of corporate social responsibility: the case of CGD - Caixa Geral de Depósitos / Portugal - Coelho, M. P. (2015)
According to the 2001 European Commission Green Paper, Social Responsibility conceptualization is associated with the idea of companies deciding, in a voluntary base, to contribute for a fair society and a cleaner environment. The tradition of social intervention in Portugal remounts to the century XV and the foundation of the Mercies. However, environmental goals were never proposed as fundamental objectives in the positioning of corporate social responsibility, given the delay of the industrial development. In spite of the tradition of practice, in informal way, of social protection by the companies of larger dimension, the appearance of “social responsibility” as an autonomous management theme, took, to some enterprises, the interest in environmental subjects, crossing a paternalist vision that put the accent in the relationships with the workers. The CGD is an example of this posture. In 2009, adhered to the Environmental Program of the United Nations for the Finance Sector (UNEP FI) becoming the first Portuguese bank to do part of this program. UNEP FI reflects the recognition of the role of this sector in the promotion of Sustainable Development: market intermediation processes have effects on investment programs and, in indirect way, impacts in the allocation of natural resources and on social tissue evolution. Scientific evidence of climatic change suggests a group of environmental, economic and social impacts, affecting CGD collaborators and customers, all over the world. An economy of smaller emissions of GEE must be built. This reality alters the logic of the economic decision, imposing new models of investment and risk management, at the same time it motivates new markets (renewable energies) and new financial solutions. CGD recognizes this situation as an opportunity and promotes, since 2007, the “Zero Carbon” Program to contribute for the reduction of the environmental impact of their activities and induce good practices to their collaborators, customers and society in general. The purpose of this communication consists of evidencing the perspective of the environmental sustainability that shapes the most general concept of the corporate social responsibility and, through the CGD case, to evaluate the potentialities and fragilities of social responsibility in this domain, in Portugal.